Analysis of GH1, GHR and PRL gene polymorphisms for estimation of the genetic diversity of Buryat and Altai cattle breeds - I. V. Lazebnaya; A. V. Perchun; B. B. Lhasaranov; O. E. Lazebny; Yu. A. Stolpovskiy (Вавиловский журнал генетики и селекции)
Small and unique Buryat and Altai cattle breeds of TuranoMongolian origin are well adapted to harsh conditions of the continental climate to be their habitat. However, the population-genetic structure of the breeds has been poorly studied. This paper presents the results of analysis of polymorphisms GH1 (AC_000176.1: BTA 19, exon 5, rs41923484, g.2141C>G, L127V), GHR (AC_000177.1: BTA 20, exon 10, rs109300983, g.257A>G, S555G) and PRL (AC_000180.1: BTA 23, exon 3, g.35108342A>G) in the samples of Buryat cattle breed of Russia, China and Mongolia, and indigenous Altai cattle breed (Russia) that belong to TuranoMongolian cattle. The Russian sample of Buryat breed was differentiated from the Mongolian sample based on pairwise G-test and FST values for the PRL-RsaI polymorphism and from the Chinese sample – based on pairwise G-test values for the GH1-AluI polymorphism. All the three samples of Buryat breed clearly differed from the sample of Altai breed based on pairwise G-test and FST values for the GHR-AluI polymorphism as well as on the base of FST values for the joint polymorphism of the three genes. Nei’s genetic distances calculated from the three gene polymorphisms also confirmed the difference between the two breeds. The results of AMOVA demonstrated that GHR gene variability (16 %) gave the largest contribution to the differentiation that was confirmed by FST values (0.12–0.27). The STRUCTURE software enabled us to reveal four clusters, with a specific ratio for each sample, in the Chinese and Mongolian samples of Buryat breed, and in the sample of Altai breed, while the Russian sample of Buryat breed had only three clusters. The differences within the breed level were determined based on the GH1-AluI and PRL-RsaI polymorphisms, while at the inter-breed level – based on the GHR-AluI polymorphism. Linkage disequilibrium analysis demonstrated significant linkage of the following pairs of genes in the Buryat breed: GH1-GHR, GH1-PRL, GHR-PRL.